Educators' beliefs about appropriate pedagogical models for Spanish-speaking ELLs who differ in home-language and English-language literacy abilities in the United States. Issue 4 (19th May 2019) - Murphy, Audrey Figueroa; Torff, Bruce; Sessions, David
ABSTRACT: Survey research ( n = 366) examined educators' beliefs about the efficacy of five pedagogical models (English as a second language ( ESL ) self-contained, ESL push-in, ESL pullout, bilingual, and dual language ) for English language learners who differ in English literacy proficiency and home-language abilities (delimited to Spanish in this research). Dual language was preferred when students have high English proficiency; this effect was extremely strong for students who are also proficient in Spanish, and moderate when students' Spanish skills are low. Bilingual education was moderately favored when English is low and Spanish is high. ESL self-contained was moderately favored when students lack literacy proficiency in both English and Spanish. Language proficiency was a consistent predictor of model preferences, with effects sufficiently strong to likely have meaningful impact on actual student placements. Future research should determine the extent to which this pattern in teachers' beliefs comports with educational outcomes.